Housing Conditions Linked to Tick (Ixodida: Ixodidae) Infestation in Rural Areas of Colombia: A Potential Risk for Rickettsial Transmission. Issue 1 (21st August 2020) - Quintero V, Juan C; Mignone, Javier; Osorio Q, Lisardo; Cienfuegos-Gallet, Astrid V; Rojas A, Carlos
Abstract: This cross-sectional study explores the different conditions related to the infestation of ticks in households and the potential risks for rickettsial transmission in Urabá, Colombia. The main outcome of interest was villagers' perception of tick infestation. The data were analyzed using a clog-log mixed regression model. Ticks were collected from infested humans to diagnose infection by spotted fever group rickettsiae (SFGR). In addition, a thematic analysis of qualitative data from key informants concerning knowledge about ticks was conducted. The prevalence of infestation of ticks in households was estimated at 60.99% (95% CI: 51.58–93.51). The multivariate model suggested that households with palm leaf roofs (PR = 1.95; 95% CI: 1.19–2.95), canines (PR = 1.76; 95% CI: 1.21–2.46), rats (PR = 2.19; 95% CI: 1.45–3.08), and with the presence of opossums in areas surrounding the households (PR = 1.51; 95% CI: 1.05–2.10) had a higher prevalence of tick infestation. Two samples of the tick species Amblyomma patinoi were found infected with Rickettsia amblyommatis and Candidatus Rickettsia colombianensi. A thematic analysis provided the names that local community members give to ticks, areas where ticks are common, and the individuals at risk of infestation. The presence of domestic, synanthropic, and wild animals suggests a high risk of the dissemination of ticks inside dwellings and close to them in these rural areas.